2017
DOI: 10.1038/pr.2017.237
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in the pathogenesis and treatment of bronchopulmonary dysplasia: a clinical review

Abstract: Advances in neonatal medicine have led to increased survival of infants born at the limits of viability, resulting in an increased incidence of bronchopulmonary dysplasia (BPD). BPD is a chronic lung disease of premature infants characterized by the arrest of alveolarization, fibroblast activation, and inflammation. BPD leads to significant morbidity and mortality in the neonatal period and is one of the leading causes of chronic lung disease in children. The past decade has brought a surge of trials investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 57 publications
0
25
0
2
Order By: Relevance
“…We have shown that MSCs in combination with EPO could attenuate lung fibrosis induced by high oxygen through inhibition of TGF‐β1/Smad signalling . Recent studies suggest that inflammation response also plays a major role in the development of BPD, therefore, it is very necessary to study whether the MSCs and EPO combination therapy can more attenuate inflammation than MSCs transplantation alone. p38 MAPK acts upstream of LPS‐induced nuclear factor‐kappa B (NF‐κB), which is a key participant in the inflammation, immune response, and regulation of cell differentiation and apoptosis during acute lung injury .…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that MSCs in combination with EPO could attenuate lung fibrosis induced by high oxygen through inhibition of TGF‐β1/Smad signalling . Recent studies suggest that inflammation response also plays a major role in the development of BPD, therefore, it is very necessary to study whether the MSCs and EPO combination therapy can more attenuate inflammation than MSCs transplantation alone. p38 MAPK acts upstream of LPS‐induced nuclear factor‐kappa B (NF‐κB), which is a key participant in the inflammation, immune response, and regulation of cell differentiation and apoptosis during acute lung injury .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies investigating the appropriate dose of IT MSCs for treatment of BPD included doses of 1×10 7 and 2×10 7 cells/kg. Both doses appeared to be safe without increased short term or long-term adverse events (31,32). Multiple studies have investigated the efficacy of IT MSCs delivery in rat BPD model, and these have typically included doses of ∼10 5 cells per rat (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…As a convenient and safe source of stem cells, it could provide regrowth to underdeveloped lung tissue of preterm infants by providing more stem/progenitor cells. In addition, its paracrine effects help to improve lung function, vascularization of the airways, and reduce fibrosis, and therefore have considerable potential for reducing lung injury in preterm infants (35)(36)(37)(38)(39)(40). However, few studies have evaluated the effects of ACBMNC infusion for prevention of BPD in extremely preterm infants.…”
Section: Discussionmentioning
confidence: 99%